A computational investigation of olive oil residues combustion in a vertical furnace. (15th July 2021) - Bayoudh, Mariem; Touati, Hazem; N'Ticha, Hmaied Ben
The paper presents a numerical investigation of combustion of pulverised olive waste and its impregnated samples. Olive oil by-products, mainly olive solid waste (OSW) and olive mill wastewater (OMWW) mixtures that are called impregnated solid waste (ISW) are investigated for different mixing ratios. The investigation is carried out by an in-house two-dimensional CFD code based on the finite volume method, developed for this purpose. The model is first validated by comparisons to the experimental data and predictions of other authors. Subsequently, it is applied to the cases of present interest, predicting the efficiency of the thermal process, species and temperature distributions. The combustion behaviour of ISW is compared with that of the original OSW under the same conditions. The findings of the present study shows that a beneficial effect of using ISW is observed, as the addition of OMWW leads to a decrease of carbon oxides production. Furthermore, the OMWW addition does not have a negative effect on their firing quality since the different samples exhibit quite close temperature profiles. Obtained results are important for the investigation the possibility of using olive residues as an alternative energy source in olive producing countries.